2021
DOI: 10.1021/acs.jpcb.1c01644
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Electric Field-Driven Active Propulsion of Patchy Microellipsoids

Abstract: Active colloids are a synthetic analogue of biological microorganisms that consume external energy to swim through viscous fluids. Such motion requires breaking the symmetry of the fluid flow in the vicinity of a particle; however, it is challenging to understand how surface and shape anisotropies of the colloid lead to a particular trajectory. Here, we attempt to deconvolute the effects of particle shape and surface anisotropy on the propulsion of model ellipsoids in alternating current (AC) electric fields. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Glancing angle vapor deposition allows the fabrication of patchy particles with even lower symmetry than the Janus hemispherical configuration. This technique was recently used to demonstrate the unique role of surface anisotropy in encoding complex motions under ac electric fields. , Spherical polystyrene microspheres coated with low-symmetry patches of gold swim in nonlinear 3D trajectories. Notably, a triangular patch allows particles to move in a helical path similar to the swimming of spermatozoa and other microorganisms .…”
Section: Self-propulsion Of Active Colloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Glancing angle vapor deposition allows the fabrication of patchy particles with even lower symmetry than the Janus hemispherical configuration. This technique was recently used to demonstrate the unique role of surface anisotropy in encoding complex motions under ac electric fields. , Spherical polystyrene microspheres coated with low-symmetry patches of gold swim in nonlinear 3D trajectories. Notably, a triangular patch allows particles to move in a helical path similar to the swimming of spermatozoa and other microorganisms .…”
Section: Self-propulsion Of Active Colloidsmentioning
confidence: 99%
“…Polystyrene ellipsoids are readily obtained by stretching spherical microparticles to a specific aspect ratio. , Such anisotropic particles can then be rendered patchy using the same metal vapor deposition techniques used for microspheres but yielding more complex patch shapes. Lee et al reported a way to fabricate and characterize such particles based on the patch asymmetry, measured from the metal coverage of the transverse and longitudinal axis of the ellipsoid . These active particles access linear, circular, and helical motions based on the type of gold patch on their surface (Figure c) .…”
Section: Self-propulsion Of Active Colloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, heterodimeric nanoclusters designed to promote specific intercluster interactions have been shown to assemble into double helical strands . Patchy microellipsoids have been recently shown to follow helical trajectories in an AC electric field . Helicity has technological implications, for example, in functional optical materials and in nanomechanical systems. Further, colloids are excellent model systems to examine the physics of self-assembly: micrometer-sized colloidal particles exhibit Brownian motion and are sufficiently large to allow visualization using optical microscopy.…”
mentioning
confidence: 99%